A Systematic Review Trend of Learning Methods for Reading the Kitab Kuning at Pesantren (2000-2022) - Muhamad Arif; Makmur Harun; Mohd Kasturi Nor bin Abd Aziz (Journal of Islamic Civilization, 2022)
This research provides a critical analysis of several methods for learning to read the yellow book (Kitab Kuning), as well as research results published in national and international databases of journals and proceedings. Regarding the study results that generate discussions on one or two methods for reading the yellow book. Starting with this, researchers are interested in conducting critical analysis with the aid of unrecorded space and the necessity for more research using a systematic literature review. As a fresh (targeted) perspective taken by academics on how Islamic educational institutions (Islamic boarding schools-non-Islamic boarding schools) established the yellow book reading method in the 21st century. In addition, researchers need precise data on the performance of the yellow book reading approach based on 21st-century study findings. This study employs qualitative methods in conjunction with a systematic literature review approach, including collecting online article data from many national and international databases. Scopus, Sciencedirect, Emerald, Crossref, and Google Scholar are other examples. The researchers employed a variety of keywords, including "the yellow book (kitab kuning) reading technique/ yellow book (kitab kuning) method", " yellow book (kitab kuning)", "Islamic boarding school/pesantren", and "how to read the yellow book (kitab kuning)/how to read the yellow book (kitab kuning)" with a range of years. 2000-2022. The outcomes of this study indicate that the yellow book reading technique in the twenty-first century is undergoing rapid advances, such as the process of maximizing a mix of ancient and modern ways, such as the Al-miftah lil ulum, Ibtida'I, Tamyiz, and Amtsilati methods. With traditional procedures, such as: sorogan, bandongan, mudzakarah, muhafadzah, talaqqi, halaqah and tarqib. Penelitian ini akan menyampaikan analisis kritis dari berbagai metode belajar baca kitab kuning, sebagaimana hasil riset yang sudah terpublikasikan pada data base jurnal/procedding nasional dan internasional. Tentang temuan hasil penelitian yang kecenderungan melakukan pembahasan pada satu atau dua metode baca kitab kuning. Berawal dari sinilah peneliti berminat untuk melakukan analisis kritis dengan dukungan adanya ruang kosong yang belum tertulis dan perlu adanya riset lanjutan (menggunakan: systematic literature review). Sebagaimana sudut pandang baru (terfokus) yang diambil peneliti tentang bagaimana trand metode baca kitab kuning yang dikembangkan oleh lembaga pendidikan islam (pesantren-non pesantren) di abad 21. Selain itu, peneliti ingin mendapatkan data akurat dari keberhasilan metode baca kitab kuning berdasarkan hasil riset di abad 21. Penelitian ini menggunakan metode kualitatif dengan pendekatan systematic literature review, yaitu dengan menggumpulkan data artikel publikasi secara online di beberapa databesed nasional dan internasional. Seperti; Scopus, Sciencedirect, Emerald, crossreff dan Google Scholar. Beberapa kata kunci yang dilakukan peneliti adalah “metode baca kitab kuning/ kitab kuning method”, “kitab kuning/ Kitab Kuning”, “tradisi pesantren/ pesantren tradition” dan “cara baca kitab kuning/ how to read the Kitab Kuning” dengan rentang tahun 2000-2022. Temuan riset ini adalah adanya trand metode baca kitab kuning di abad 21 mengalami perkembangan yang cukup pesat seperti proses optimalisasi dari kombinasi metode tradisional dan modern seperti metode Al-miftah lil ulum, Ibtida’I, Tamyiz dan Amtsilati. Dengan metode tradisional, seperti: sorogan, bandongan, mudzakarah, muhafadzah, talaqqi, halaqah dan tarqib.